N-Acetyl cysteine does not improve repeated intense endurance cycling performance of well-trained cyclists - Christensen, P. M.; Bangsbo, J. (European Journal of Applied Physiology, 2019)
Purpose: To evaluate the effect of antioxidant supplementation on intense endurance exercise performance and the physiologic exercise response acutely and in early recovery. Methods: Well-trained cyclists (n = 11, peak VO2: 69 ± 7 ml/min/kg) completed two identical standardized 20-min warm-up periods (WU-1 and WU-2) prior to two performance tests (PT) with a duration of ~ 4 min representing a qualifying (PT-1) and final race (PT-2) on the same day separated by 90 min. Subjects were supplemented orally with placebo (PLA) and N-acetyl cysteine (NAC; 20 mg/kg) before exercise in a double-blinded crossover design. Results: Mean power during PT-1 did not differ (P = 0.39) between PLA (400 ± 44 W) and NAC (401 ± 44 W) as was the case during PT-2 with similar performance (P = 0.74) between PLA (401 ± 43 W) and NAC (400 ± 42 W). Subjective "readiness" was lowered by prior exhaustive exercise from PT-1 to PT-2 (P = 0.012) in both PLA and NAC. Plasma total antioxidant capacity was not affected by supplementation and prior exhaustive exercise (respective main effects: P = 0.83 and P = 0.19) which also was observed for peak VO2 at ~ 5 L/min (P = 0.84 and P = 0.30). In WU-1 and WU-2, both cycling economy at ~ 20% (P = 0.10 and P = 0.21) and plasma potassium at ~ 5 mmol/L (P = 0.46 and P = 0.26) were unaffected by supplementation and prior exercise. Conclusions: Athletes executing maximal efforts of a ~ 4-min duration twice daily, as seen in track cycling, appear to gain no benefit from oral NAC supplementation on acute and subsequent performance following short-term recovery. Moreover, well-trained cyclists exhibit rapid recovery from a single bout of intense endurance cycling.